Declínio da função pulmonar em crianças e adolescentes com bronquiolite obliterante pós-infecciosa: um estudo de longo prazo prospectivo - Mariana de Fatima Viana Pimenta (2012)
Introduction: Pulmonary function testing in children and adolescents with post- infectious bronchiolitis obliterans (BO) is important in the diagnosis and follow up of patients. Objectives: Review the principal tests for the evaluation of pulmonary function parameters and studies on lung function in children and adolescents with post- infectious bronchiolitis obliterans. Data source: A non-systematic review of the literature in the last 30 years was carried out using the databases Pubmed, Lilacs, Ibecs, Biblioteca Cochrane and HighWare. Data synthesis: For uncooperative infants, the techniques most used are those which utilize forced expiratory, and forced deflation and the rapid thoracic compression method; by partial forced expiratory maneuvers, or using high volumes. Regardless of the method used, in dealing with BO, the infants already demonstrate airway obstruction in the initial phases of the disease. In children older than 5 years, the evaluation of lung function is routinely done with a spirometry and the measurement of lung volumes. Based on the data analysis of 335 patients, the presence of obstructive lung disease was noted among 50% to 100% of them. The significant response after bronchodilator administration showed a large amplitude, from 1% to 48% of evaluated patients. The studies that evaluated lung volumes demonstrated an increase in total lung capacity, the ratio between residual volume and in total lung capacity and resistance, with hyperinflation and air trapping. Conclusions: The majority of studies, using diverse techniques to measure lung function, ranging from infants to adults, demonstrated the same pattern of airway obstruction and the variation of the response after bronchodilator administration was not significant for the most part.